Tax Compliance Strategies and Revenue Generation in Nigeria - Mustafa Salih Dakhil; Muyiwa Emmanuel Dagunduro; Faraj Gheni Abbood; Gbenga Ayodele Falana (Economy, Business and Development: An International Journal (EB&D), 2025)
Tax revenue generation is crucial for economic management and development in both developed and developing countries, as it supports public services, infrastructure, and social programs, thus fostering sustainable development and economic stability. This study aims to investigate the effect of tax compliance strategies on tax revenue generation in Nigeria, assessing the effectiveness of different approaches in closing the tax gap and boosting government revenue. This study used a survey research design to explore relationships between variables without manipulation, providing valuable insights into their connections. Primary data were collected through a structured questionnaire from 3,784 tax officials at the Federal Inland Revenue Service (FIRS) in the southwest states of Nigeria, considered knowledgeable about the subject as of December 31, 2023. The questionnaire employed a five-point Likert scale (Strongly Agree to Strongly Disagree) to gather responses. The reliability and validity of the instrument were assessed using both statistical methods, like Cronbach's Alpha, and non-statistical methods. Data analysis involved descriptive statistics (mean, variance, skewness, kurtosis) and inferential statistics (correlation and regression analysis) to summarize and interpret the data. The empirical analysis reveals that both voluntary tax compliance and tax enforcement strategies significantly contribute to increasing tax revenue generation in Nigeria. This study concludes that a combined approach of encouraging voluntary tax compliance and implementing strong enforcement strategies is effective in increasing tax revenue generation in Nigeria. Based on the outcomes of this study, this study recommends that government should invest in comprehensive taxpayer education programs that clearly explain tax laws, the importance of compliance, and the benefits of paying taxes.
Keywords: H20; 330; Tax compliance strategies; tax enforcement strategy; tax revenue generation; voluntary tax compliance strategy